Shifting The Paradigm: Nepal as a Potential Leader in The Field of Medical Education - Karmacharya, Dr Biraj Man (Kathmandu University Medical Journal, 2012)
No abstract available. http://dx.doi.org/10.3126/kumj.v9i1.6247 Kathmandu Univ Med J 2011;9(1):1-2